2014
DOI: 10.1155/2014/186826
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Cerebellar Liponeurocytomas: Case Report and Literature Review

Abstract: Cerebellar liponeurocytomas were recognized in the 2000 WHO 3rd edition of CNS tumors as a distinct grade I pathological entity, a tumor with a more favorable prognosis than medulloblastoma. But reports of long-term recurrences and some possible aggressive behavior led to an upgrade on the latest WHO 4th edition of CNS tumors. The case of a 64-year-old female patient is reported in this paper. More than 30 cases of this lately recognized pathological entity have been reported to date. The diagnostic, radiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…The roles of adjuvant chemotherapy and radiation have not been established. 18 In the current cases, lesions from the patient and her mother had comparable immunohistochemical profiles, including variable expression of synaptophysin, MAP-2, NeuN, neurofilament, GFAP, and vimentin. The patient's tumor appeared more differentiated, with a greater lipidized component and stronger expression of neuronal markers.…”
Section: Discussionmentioning
confidence: 56%
“…The roles of adjuvant chemotherapy and radiation have not been established. 18 In the current cases, lesions from the patient and her mother had comparable immunohistochemical profiles, including variable expression of synaptophysin, MAP-2, NeuN, neurofilament, GFAP, and vimentin. The patient's tumor appeared more differentiated, with a greater lipidized component and stronger expression of neuronal markers.…”
Section: Discussionmentioning
confidence: 56%
“…Oudrhiri et al ., in 2013, in his paper, reviewed 36 previously reported cases of liponeurocytoma and found that the average age of occurrence of this lesion was 49 years (range 32–79 years) with a female preponderance (1.8:1). [8] Recent reports also exist in the form of individual cases, the most common being in the infratentorial location. [910111213] Gembruch et al ., in a systematic review of all the reported cases ( n = 73) until 2018, noted that these tumors had low MIB-1 proliferation index (3.73 ± 4.01%).…”
Section: Discussionmentioning
confidence: 99%
“…Like the cerebellum liponeurocytoma in the CPA tumors, the average age of the onset of this tumor is between the third to fifth decades of life with equal preva-lence in men and women [9]. In the study of 7 cases of liponeurocytoma, 4 patients were male and 3 were female [3,7,[9][10][11][12]. Our patient was a 27-year-old woman.…”
Section: Discussionmentioning
confidence: 99%
“…It is predominantly located in the posterior cranial fossa and characteristically emerging in adults. Lipidized medulloblastoma, lipomatous medulloblastoma and neurolipocytoma are different names that have been considered for this tumor in the past [3,4]. Histopathological examination of the tumor cells presented lipidized cells are found between small neoplastic cells with focal lipomatous differentiation.…”
Section: Background and Importancementioning
confidence: 99%